The Impact of Digital Technology on the Effectiveness of Recruitment and Selection of Young Human Resources in Mataram City - Chasanah, Afrida Nur; Septika, Baiq Herdina; Wulandari, Yayang (Business Management, 2025)
The advancement of digital technology has significantly transformed recruitment and selection processes, particularly among tech-savvy youth. Mataram City, as the economic and educational hub of West Nusa Tenggara Province, is predominantly populated by digitally native young people. This study aims to analyze the influence of technology use on candidate experience and selection effectiveness among young job seekers in Mataram. Employing a quantitative associative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 150 respondents aged 18–30 who had participated in technology-based recruitment processes. The findings reveal that the use of technology has a positive and significant effect on candidate experience (β = 0.42; p < 0.01) and selection effectiveness (β = 0.38; p < 0.01). Additionally, candidate experience significantly influences selection effectiveness (β = 0.55; p < 0.01). These results emphasize that integrating technology into recruitment not only improves process efficiency but also enhances candidate engagement and the overall quality of selection. This study provides practical insights for companies in designing digital recruitment strategies that align with the characteristics of the younger generation.